1998
DOI: 10.1007/bf02415229
|View full text |Cite
|
Sign up to set email alerts
|

Critical heat fluxes when boiling occurs in a nonuniform heat-releasing porous medium

Abstract: An analysis of the aftereffects of the accident at the Three Mile Island (USA) nuclear power plant revealed the importance of heat and mass transfer in a heat-releasing porous medium for reactor safety [1]. The interaction of a porous heat-releasing bed with the body of the reactor is now considered to be one of the possible stages of serious accidents in lightwater reactors with a loss of cooling ability in the active zone [2]. The main danger for the body of the reactor is a thermal attack by molden material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Experimental results (Décossin, 2000;Konovalikhin et al, 2000) have shown that two-dimensional effects due to heterogeneities in the bed or at the boundaries may increase significantly the critical heat flux. At the same time, new two-dimensional theoretical models, such as DECO-2D (Likhanskii et al, 1998) and WABE-2D (Mayr et al, 1998), presented the same trends. The present paper brings complementary results that confirm the previous observations and show the necessity to take into account multi-dimensional effects in order to properly calculate dryout or reflooding in a debris bed.…”
Section: Multi-dimensional Effectsmentioning
confidence: 69%
“…Experimental results (Décossin, 2000;Konovalikhin et al, 2000) have shown that two-dimensional effects due to heterogeneities in the bed or at the boundaries may increase significantly the critical heat flux. At the same time, new two-dimensional theoretical models, such as DECO-2D (Likhanskii et al, 1998) and WABE-2D (Mayr et al, 1998), presented the same trends. The present paper brings complementary results that confirm the previous observations and show the necessity to take into account multi-dimensional effects in order to properly calculate dryout or reflooding in a debris bed.…”
Section: Multi-dimensional Effectsmentioning
confidence: 69%